Gender, religiosity, and fraud: The role of unethical behavior as mediation - Yesi Mutia Basri; Sabrina Ardhya Putri Rahmola; Hariadi (Jurnal Akuntansi dan Auditing Indonesia, 2022)
The government is an institution that cannot be separated from fraud cases. This study analyzed how gender and religiosity affect fraud with unethical behavior as mediation. The population in this study was the State Civil Apparatus in the Pekanbaru City Government. Through a purposive sampling technique, the researcher found that 380 National Civil Apparatuses participated in this study. The questionnaire was sent directly to the respondents to collect the data. Meanwhile, the data was analyzed by WarpPLS 6.0. The finding shows that gender and religiosity influence unethical behavior and fraud. There are behavioral differences between men and women in behavior that affect fraud. Women behave more ethically, which shows a low level of fraud. The officials who have a high level of religiosity will behave more ethically and can lower the level of fraud. This study also proves that unethical behavior can mediate the relationship between gender and religiosity. It has also contributed to the government conducting ethics training for the country's civil apparatus.